Advanced Imaging Techniques for Assessing Fat, Iron, and Fibrosis in Chronic Liver Disease - Sabarish Narayanasamy; Manuela Franca; Ilkay S. Idilman; Meng Yin; Sudhakar K. Venkatesh (Gut and Liver)
Imaging plays a critical role in the management of chronic liver disease (CLD) because it is a safe and painless method to assess liver health. The widely used imaging techniques include ultrasound, computed tomography and magnetic resonance imaging. These techniques allow the measurement of fat deposition, iron content, and fibrosis, replacing invasive liver biopsies in many cases. Early detection and treatment of fibrosis are crucial, as the disease can be reversed in its early stages. Imaging also aids in guiding treatment decisions and monitoring disease progression. In this review, we describe the most common imaging manifestations of liver disease and the current state-of-the-art imaging techniques for the evaluation of liver fat, iron, and fibrosis.